Violência e crimes políticos: estudo centrado na teoria fundamentada e análise de redes sociais - França, André Luiz Dias de (2019)
This doctorate research deals about the dictatorial period in Brazil between the years 1964- 1985 and its associated network of perpetrators. To achieve the research’s objective, it was applied two complementary approaches: Grounded Theory and Social Network Analysis (SNA). The first approach was aimed to explore the research object and to better understand about the dictatorial period and their main characters. Initially, was consulted the reports of Comissão Nacional da Verdade (National Truth Commission) to obtain the name of the perpetrators and list the categories to understand the scenario and position of each individual. The first premise established was: It is possible to draft a relationship between any pair of actors through a document analysis. With this statement, was performed a deep research at the Sistema de Informação do Arquivo Nacional (National Archive Information System). There, was found thousands of documents about the protagonists of that period. To analyze the recovered document, it was applied text mining techniques to verify the frequency of relationship among actors. The Social Network Analysis approach grounded the level of connections and allowed the discovery of the network structure and its importance to support the dictatorship period in Brazil.